An unusual presentation of encephalitis which mimicked generalised tetanus - Benny, Anushree M.; Nagar, Rajendra Prasad; Nagori, Gautam Lal (International Journal of Contemporary Pediatrics, 2021)
Movement disorders are frequent mimickers of more severe neurological presentations, whenever it is diagnosed one should suspect a central nervous system infection as an underlying cause. A 11 year old girl presented in casuality with intermittent generalised muscle spasm, clear sensorium, trismus and risus sardonicus. Initially managed as a case of tetanus, rapid resolution of spasms made suspicion of encephalitis as underlying cause of dystonia which mimicked tetanus. Blood investigation and CSF analysis were normal. CECT brain showed hyper dense lesions bilateral temporal lobes suggestive of viral encephalitis. Child was managed with intravenous acyclovir and dexamethasone after which child improved considerably. Acute dystonia is a close mimicker of tetanus. Any patient presenting with new onset movement disorder should be investigated for central nervous system infection even though it has been reported as a rare cause for the same.